High Pressure Processing: A Novel Seafood Preservation Approach - Ikbal, Asik; Bhattacharya, Ankures; Chowdhury, Supratim (Chronicle of Bioresource Management, 2021)
In modern days, consumers are keen to buy convenient, minimal processed fresh food with high nutritive quality and safety. But, the most of the techniques in food processing are using heat treatment to improve the shelf life of the product. As a result, reduction in nutritional qualities i.e., loss of texture, colour, flavour, odour and also undesirable changes in the product have been noticed in these conventional preservation and sterilization. In this context, non thermal food processing techniques are useful to reduce these problems and also process good quality food products. Thus, high pressure processing emerges as the most convenient, which can make safe food and also preserve the qualitative parameters of foods. It can reduce the vegetative microorganism load which are the primary reasons for food borne illness. Hence, high pressure processing provides a novel approach to food technologists to procure foods with minimally processed and superior quality.